Empirical Legal Investigation of Land Disputes: The Case of Rantau Pandan, Bungo Regency - Suhermi, Suhermi; Hasan, Umar; Sasmiar, Sasmiar; Manik, Herlina (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
Land is a very basic human need for humans to live and carry out activities on land so that at all times humans are always in contact with land, it can be said that almost all human life activities, either directly or indirectly, require land. The emergence of land dispute cases in Indonesia is no exception in Rantau Pandan District, Bungo Regency, of course clear regulations or legal instruments are needed to ensure legal certainty for the owners of the land. The aim of the research is to find out and analyze the factors that cause land disputes and how to resolve land disputes that occur in the community in Rantau Pandan District, Bungo Regency. The type of research used is empirical juridical using primary data sources, namely data obtained directly in the field through interviews with respondents and informants and secondary data in the form of regulations, textbooks, journals and traditional seloko. Based on the data, it was found that the factors causing land disputes in the Rantau Pandan District, Bungo Regency, were caused by inheritance factors and unclear land boundaries. The method for resolving land disputes is by deliberation using Customary Law in ascending and descending stages.